Dantrolene Administration in the Management of the Prehospital Patient with Methylenedioxymethamphetamine Overdose: A Case Series and Literature Review - Kia Nikoomanesh; Alexander T. Phan; Julian Choi; Sarkis Arabian; Michael M. Neeki (Case Reports in Critical Care)
Methylenedioxymethamphetamine (MDMA) is a psychoactive substance that is used commonly as a recreational drug at rave music festivals. MDMA intoxication can cause a myriad of symptoms and side effects including the manifestation of hyperpyrexia in patients. Hyperpyrexia can mimic a heat stroke and ultimately lead to various forms of end-organ damage. The most common methods used in treating MDMA-induced hyperpyrexia focus on the rapid reduction of core body temperature. Various off-label medications have also been used in combating MDMA-induced hyperpyrexia. Dantrolene is one such medication, although its role in the treatment of MDMA intoxication remains uncertain. This case series preliminarily examines the efficacy of dantrolene in mitigating MDMA-induced hyperpyrexia and potentially reducing the risk of end-organ damage in patients suffering from MDMA overdose. This study focuses on nine patients who presented after ingesting various forms of MDMA at “rave” music events. All patients were found to be hyperthermic in the field with a maximum core body temperature of 109 degrees Fahrenheit. All patients were immediately managed by cooling measures, and seven patients additionally received dantrolene in the field before being transferred to Arrowhead Regional Medical Center. Upon arrival to the hospital, nearly every patient was found to have significantly decreased body temperatures when compared to previously measured body temperatures out in the field. However, nearly all patients in the study were also noted to have laboratory abnormalities consistent with various forms of end-organ damage. The degree and severity of end-organ damage observed in MDMA-induced hyperpyrexia seem to be a function of initial core body temperature. Higher core body temperature tends to correlate with more forms of end-organ damage and a higher severity of end-organ damage. Intervention with dantrolene and cooling measures appeared to have no effect on reducing the risk of developing end-organ damage in this patient population.